Cultivation of Genovese basil (Ocimum basilicum L. cv. Genovese) in aquaponic and hydroponic systems: A comparative study - Annabi, Hibat Allah; Laribi, Bochra; Bettaieb, Taoufik (Journal of Agriculture and Applied Biology, 2025)
Recently, many horticultural crops have been subjected to study under hydroponic and aquaponic conditions, with a view to enhance their productivity. Nevertheless, a comparative analysis of these two soilless cultivation systems has rarely been undertaken, despite the fact that they represent two distinct approaches. This study’s objective was to compare between the aquaponic cultivation system and the hydroponic one, with the aim of identifying the most suitable soilless system for cultivating Genovese basil (O. basilicum L. cv. Genovese). For the purpose of this study, a factorial randomized complete block with three repetitions was conducted. It was carried out at the National Agronomic Institute of Tunisia under glasshouse conditions. Accordingly, the variation of the soilless cultivation systems effects was determined by measuring and evaluating plant growth, biomass production and photosynthetic performance of basil. Main results showed that plant height (25.69 ± 2.87 cm/plant), length of internodes (2.47 ± 0.17 cm/plant) and leaves number (10.89 ± 1.02 leaves/plant), fresh and dry weight of shoots (9.17 ± 0.49 g and 1.03 ± 0.05 g, respectively) and roots (5.22 ± 0.14 g and 0.37 ± 0.03 g, respectively) were significantly higher in aquaponically grown plants in comparison to hydroponics. However, no significant differences were noted between aquaponics and hydroponics regarding the shoot and root dry matter contents. In addition, the content of chlorophyll a (44.59 ± 3.42 µg∙mg-1 FW) and the efficiency of the photosystem II (Fv/Fm) (0.83 ± 0.01) were significantly higher in basil grown in aquaponics when compared to the hydroponic system. Overall, these findings indicate that aquaponics seems to be more suitable for growing basil plants than the hydroponic system.